2005
DOI: 10.2174/1381612054021006
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels and Epilepsy

Abstract: The role of voltage-gated and ligand-gated ion channels in epileptogenesis of both genetic and acquired epilepsies, and as targets in the development of new antiepileptic drugs (AEDs) is reviewed. Voltage-gated Na+ channels are essential for action potentials, and their mutations are the substrate for generalised epilepsy with febrile seizures plus and benign familial neonatal infantile seizures; Na+ channel inhibition is the primary mechanism of carbamazepine, phenytoin and lamotrigine, and is a probable mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(79 citation statements)
references
References 115 publications
(279 reference statements)
0
70
0
9
Order By: Relevance
“…GABAB receptors differ from GABAA receptors by their structural and functional properties, but also exhibit numerous pharmacological effects, including central muscle relaxation, epileptogenesis, suppression of drug craving, antinociception, cognitive impairment and inhibition of hormone release [12,239].…”
Section: Gabab Receptorsmentioning
confidence: 99%
“…GABAB receptors differ from GABAA receptors by their structural and functional properties, but also exhibit numerous pharmacological effects, including central muscle relaxation, epileptogenesis, suppression of drug craving, antinociception, cognitive impairment and inhibition of hormone release [12,239].…”
Section: Gabab Receptorsmentioning
confidence: 99%
“…A tricyclic anticonvulsant, carbamazepine inhibits voltage dependent sodium channels and activates the voltage-dependent potassium channels [66]. It has been found to suppress withdrawal-induced kindling in limbic structures [67] [68], and animal studies have also shown that carbamazepine is able to prevent alcohol withdrawal seizures [69] in addition to decreasing withdrawal symptoms [70].…”
Section: Carbamazepinementioning
confidence: 99%
“…Novel susceptibility genes for FS, ADEFS+ and SMEI may exist in these loci. Fourteen loci common to all phenotypes may play a role in epileptogenesis [39], while genes located in loci belonging to Area I (5), Area II (3) and Area III (2) multi-factorial disorder because they are provoked by high fever or, in cases of SMEI, the first seizures are mostly associated with fever [10]. These data suggest that FS, ADEFS+ and SMEI represent a continuum of epileptic disorders; FS is the mild type, SMEI is the most severe type, and ADEFS+ is an intermediate phenotype between FS and SMEI spectrum.…”
Section: Loci Significantly Associated With Fs Adefs+ and Smeimentioning
confidence: 99%